2016
DOI: 10.11606/issn.1678-4456.v53i1p72-87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary nitrogen source and crude protein content on nitrogen balance and lactating performance of dairy cows

Abstract: The aim of the present study was to evaluate the effect of two crude protein contents (CP) and two main nitrogen sources in the diet of dairy cows, using sugarcane as forage, on intake, total apparent digestibility, milk yield and composition, and nitrogen balance. Twelve Holstein cows in late lactation were assigned in three contemporary square, in a Latin Square design 4 × 4, with 2 × 2 factorial treatment arrangement, in 21-day trial by period, 14 for diet adaptation and the last seven for sampling and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We found here that the increase in ruminal ammonia N concentration was directly associated with the observed plasma urea concentration ( Figure 1 a). In agreement with our findings, Migliano et al [ 59 ] likewise reported a strong positive correlation between ruminal ammonia N and plasma urea N. The inclusion of improved forages in TMR diets might contribute to highly degradable protein sources that decreased ruminal ammonia N concentrations, but ruminal ammonia N likely remained adequate for microbial growth [ 60 ]. The ruminal pH that we obtained is normal for lactating dairy cows fed roughage-based diets [ 52 ], perhaps because the dietary NDF concentrations of all of the dietary treatments were sufficient to maintain the optimal ruminal pH for cows fed high-forage diets.…”
Section: Discussionsupporting
confidence: 91%
“…We found here that the increase in ruminal ammonia N concentration was directly associated with the observed plasma urea concentration ( Figure 1 a). In agreement with our findings, Migliano et al [ 59 ] likewise reported a strong positive correlation between ruminal ammonia N and plasma urea N. The inclusion of improved forages in TMR diets might contribute to highly degradable protein sources that decreased ruminal ammonia N concentrations, but ruminal ammonia N likely remained adequate for microbial growth [ 60 ]. The ruminal pH that we obtained is normal for lactating dairy cows fed roughage-based diets [ 52 ], perhaps because the dietary NDF concentrations of all of the dietary treatments were sufficient to maintain the optimal ruminal pH for cows fed high-forage diets.…”
Section: Discussionsupporting
confidence: 91%
“…nitrogen in the milk is indicative of a de ciency in the fermentation of non-ber carbohydrates, an excess of crude protein in the diet and/or imbalance between the availability of energy and nitrogen in the rumen. Migliano et al (2016) evaluating the use of sugarcane-based diets with high and low concentrations of CP (13 vs. 14.8%) observed higher urea nitrogen in the milk from diet based with 14.8% CP content, and similar DMI, milk production and ef ciency of dietary nitrogen. The cows fed the CS based diets, produced milk numerically higher in SCC than the animals that received the diet based on CSSC (P≥0.05).…”
Section: Foragementioning
confidence: 97%
“…If the availability of nitrogen exceeds the need for rumen microorganisms, this excess will be converted to ammonia. The ammonia formed is then absorbed through the rumen wall epithelium and taken to the liver and converted to urea then excreted through the renal or milk production (Migliano et al, 2016). Dry matter intake (DMI) is affected by protein or nitrogen intake.…”
Section: Introductionmentioning
confidence: 99%